THE UTILIZATION OF THE HOME DEVELOPMENT AS A LIVING PHARMACY - SURI AMILIA; Mutia Dewi; Safurida (Global Science Society, 2021)
This community service activity is carried out at Gampong Karang Anyar, Kecamatan Langsa Baro, Kota Langsa which aims to: (1) provide socialization to housewives about types of traditional medicinal plants that are beneficial to health, (2) provide motivation to use yards for plants traditional medicines, (3) the use of used materials as a medium for planting traditional medicines in the yard of the house. This outreach activity was carried out by means of lectures and discussions as well as questions and answers. And training is carried out on how to plant and seedlings, and the use of used goods as a medium. The results achieved were that the socialization and training activities received positive appreciation from the village apparatus and the surrounding community, namely from the licensing process to implementation which fully supported the activities carried out. The community is also very enthusiastic in participating in this socialization and training activity because they want to become a healthy community.